Pemanfaatan Lahan Kosong dengan Konsep Penghijauan dalam Meningkatkan Upaya Pelestarian Lingkungan di Kelurahan Tanah Merah - Zahtamal Zahtamal; Anisa Nur Eksanti; Arwina Pratiwi Kuswoyo; Asmita Meilani; Dwi Kurniawati R; Elvina Carolina; Miftahul Kurniawan; Muhammad Agus Setiawan; Muliyono Muliyono; Sri Retno Pramesti; Zulkifli Zulkifli (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Tanah Merah Village is one of the Villages in Pasir Penyu District, Indragiri Regency, Riau Province, Indonesia. One of the problems faced by the people of Tanah Merah Subdistrict is that land utilization is still lacking, vegetation is still lacking, the existing land is predominantly overgrown with grass. The community service methodology carried out begins with coordinating with village officials, surveying the location of empty land, determining planting locations, distributing seeds to the community, and planting seeds together on empty land. The results showed that 500 seeds consisting of 3 types of plant seeds were planted. The aim of this activity is to help reforest empty land and raise public awareness of the importance of protecting the surrounding environment and the importance of reforestation for the environment.